Quantitative evaluation of overlaying discrepancies in mobile augmented reality applications for AEC/FM. (January 2019) - GOMEZ-JAUREGUI, Valentin; MANCHADO, Cristina; DEL-CASTILLO-IGAREDA, Jesús; OTERO, Cesar
Highlights: Most Mobile Augmented Reality (MAR) systems lack of overlaying accuracy and precision. MAR errors are due to tracking (positioning/orientation) and image processing (projection/distortion). The Drift-Vibration-Threshold function (DVT) filters the drift suffered by sensor systems. This new methodology mathematically performs a quantitative evaluation, in world coordinates, of overlaying discrepancies on the screen. Abstract: Augmented Reality (AR) is a trending technology that provides a live view of the real and physical environment augmented by virtual elements, enhancing the information of the scene with digital information (sound, video, graphics, text or geo-location). Its application to architecture, engineering and construction, and facility management (AEC/FM) is straightforward and can be very useful to improve the on-site work at different stages of the projects. However, one of the most important limitations of Mobile Augmented Reality (MAR) is the lack of accuracy when the screen overlays the virtual models on the real images captured by the camera. The main reasons are errors related to tracking (positioning and orientation of the mobile device) and image capture and processing (projection and distortion issues). This paper shows a new methodology to mathematically perform a quantitative evaluation, in world coordinates, of those overlaying discrepancies on the screen, obtaining the real-scale distances from any real point to the sightlines of its virtual projections for any AR application. Additionally, a new utility for filtering built-in sensor signals in mobile devices is presented: the Drift-Vibration-Threshold function (DVT), a straightforward tool to filter the drift suffered by most sensor-based tracking systems.